Does tourist guides’ perceptions of quality of work life effect their perceptions of responsible tourism? - Aylan, Serkan; Bayraktar, Sukran Nur (Journal of Tourism Management Research, 2024)
The rapid development of tourism movements in recent years has brought to the fore concerns about the economic, socio-cultural, and environmental carrying capacities of tourism destinations. Sustainable tourism policies, like responsible tourism, should be adopted by countries that see the significance of building tourism around pristine natural and cultural resources. This will help to pass on their values to future generations and ensure that they continue to generate economic benefits. It is important to determine the responsible tourism perceptions of tourist guides, who are important stakeholders in the tourism industry and are conscious of the protection of the natural environment in the tours they manage. In this context, it is aimed at determining whether tourist guides’ perceptions of the quality of work life have an impact on their perceptions of responsible tourism. For this purpose, first a conceptual framework was developed, and then data from the study were collected from 405 tourist guides with face-to-face surveys that contained the Work-Related Quality of Life Scale (WRQoL) and the Scale of Responsible Tourism (SRT). The study’s data were analyzed with a statistical package program and discussed in terms of descriptive and inferential statistics. As a result of the analysis, it has been determined that there is a significant relationship between the perceptions of quality of work life and the perceptions of responsible tourism of tourist guides. In addition, with the regression analysis, it was seen that quality of work life perceptions positively affected the responsible tourism perceptions of tourist guides.